Epidemiological Study on Three Hundred Patients of Scabies in the Industrial Area of Dhaka, Bangladesh (Journal of Monno Medical College, 2024)
Background: Scabies is a common and highly contagious skin disease caused by a mite called sarcoptes scabiei.Objective:  The aim of this study was to analyze the epidemiological factors associated with scabies infection in an industrial area.Methodology: Write the study design, study place, study period and study population here. It was considering age, sex, occupation, economical condition, educational status, family history of scabies of the selected patient.Results: The age group of 1 to 10 years (28.66%) and low socioeconomic condition (58.66%), illiterate (Primary 44.00%), overcrowding living (Madrasah 37.33%) showed the highest infestation rates. Write more findings hereConclusion: In conclusion an improvement of socio-economic conditions, improve living facilities, education, social awareness may contribute to a reduction in the number of scabies infections.Journal of Monno Medical College June, 2024; 10 (1):13-16